THE POSITION OF WATER AND RIVER IN CLASSICAL PERSIAN LITERATURE - Zulyeno, Bastian (International Review of Humanities Studies, 2019)
Water is one of the four elements (water, fire, soil and wind) that are most important in the history of human civilization. In the history of literature and religions in the world, water in the general picture is symbolized as a purification medium for humans to achieve happiness in life. For example, the story of the journey of Iskandar Zulkarnain and the Prophet Khidir in searching for springs of life, as well as the Prophet Moses who was washed away in the Nile, and so forth many stories and legends related to water. The Euphrates and Tigris rivers are two rivers whose water flows for a Mesopotamian civilization, even Babylon which became the capital at that time was built right on the banks of the Euphrates river. Rivers in the water system are included in the physical form of fresh water, in addition to ponds, rain and reservoirs. Where there is a river there must be life flowing with it, so that from clear water also appear phrases and terms like clear mind, light and holy, because the symbol of clarity in all things is always represented by the clearness of water. This paper will discuss how water including the river inspires Persian writers and poets in writing his works. In this paper only two poets focused on Jalaluddin Rumi and Hafez.